Pre-harvest ethephon application and training systems affect colour development, accumulation of flavonoids and fruit quality of ‘Cripps Pink’ apple - Shafiq, M.; Singh, Zora; Khann, A.S. (Southern Cross Publishing, 2014)
Poor red blush development on the surface of apple (Malus domestica Borkh.) fruit at commercial harvest causes serious economic losses to apple growers. The effects of pre-harvest spray application of ethephon and different training systems (TS) on development of red blush, accumulation of flavonoids in the fruit skin and quality of ‘Cripps Pink’ apple were investigated for two consecutive years (2004-05). ‘Cripps Pink’ apple trees trained as vase (VS), spindle bush (SB), central leader (CL), and double row (DR) TS were sprayed with single dose of ethephon (480 g L-1) 18 days prior to anticipated commercial maturity (CM). Spray application of ethephon significantly improved percent red blush, concentrations of total anthocyanin and cyanidin 3-galactoside in the fruit skin, irrespective of TS in both years. Chroma value and hue angle of the fruit colour were also significantly improved with pre-harvest spray application of ethephon.